The industrial location and the growth of the automotive industry: A systematic literature review - Jesús Guizado Cullanco, Alberto (2024)
The research analyzes the linkage between industrial location and the growth of the automotive industry. Employing a descriptive qualitative approach, 35 articles from databases such as Scopus and ScienceDirect were analyzed using the PRISMA declaration method. Three key aspects were identified: (i) human capital, (ii) access to raw materials, and (iii) technological infrastructure. The results reveal a significant positive trend, where industrial location not only increases production but also drives innovation and competitiveness in the sector. This study highlights how strategic location and logistic infrastructure are crucial for the development of the automotive sector, enhancing its adaptability and competitiveness in a global market. The research underscores the importance of strategic and economic factors in location decisions, emphasizing their impact on productive efficiency and global economic dynamics. Particularly, these findings are vital for emerging economies, as they offer key insights for enhancing their industrial and economic development in the context of globalization.